The Effect of Local Tax Revenue and Levies to Increase Revenue in Lamongan - Darmayanti, Novi (JOURNAL OF ECONOMIC SCIENCE, 2015)
This study aims to determine (1) Is there any effect of local tax revenue to increase revenue in Lamongan, (2) Is there an influence acceptance levies to increase revenue in Lamongan, (3) Is there an effect of local tax revenue and levies to increase revenue in Lamongan. Â This type of research used in this study is a quantitative approach that is ex post facto that is studying the facts that already exist. Describe a process by way of interpreting the data that has been processed. The data used in this study is a time series data (time series) during in 2008 to 2012 from January to December of the data include: local taxes, levies and revenue Lamongan. The analysis used in this study is a multiple linear regression analysis to see how much local tax revenue and levies affecting the increase in revenue earned Lamongan. The results of multiple linear regression analysis showed that local taxes and levies positive effect of increasing revenue Lamongan, this can be seen from the magnitude of the tax variable regression coefficient is greater than the variable levies is 1.358. Thus, the tax variable has the most dominant influence on the increase in revenue in Lamongan.